The economics of marriage in North Africa - Ragui Assaad; Caroline Krafft (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Marriage is the single most important economic transaction and social transition in the lives of young people. Yet little is known about the economics of marriage in much of the developing world. This paper examines the economics of marriage in North Africa, where asymmetric rights in marriage create incentives for extensive up-front bargaining and detailed marriage contracts. As well as describing the limited literature on the economics of marriage in North Africa, this paper draws on economic theories of the marriage market and game-theoretic approaches to bargaining to propose a unifying framework for the economics of marriage in North Africa. New empirical evidence is presented on the economics of marriage in Egypt, Morocco, and Tunisia, illustrating how individuals' characteristics and ability to pay shape bargaining power and marriage outcomes, including age at marriage, marriage, costs, consanguinity, and nuclear residence.
Keywords: J12; J16; N37; C78; 330; economics of marriage; marriage market; marriage contract; bargaining; North Africa; age at marriage; marriage costs; consanguinity; nuclear residence